HUBUNGAN PAJANAN PESTISIDA DENGAN IQ ANAK SEKOLAH DASAR DI DESA KOPENG KECAMATAN GETASAN, KABUPATEN SEMARANG - Cresti Dwitiya Murti; Yusniar Hanani Darundiati; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pesticide using in Indonesia is still uncontrolled. The impact of pesticide contamination not only in adult but also in children. The aim of this research was to determine the association between history of pesticide exposure on elementary children’s IQ at Kopeng village, Getasan subdistrict, Semarang regency.The method of this research was an observation research with a cross sectional approach. The population was children of 4th and 5th grade of Kopeng 02 elementary wich total is 21 students, and the sample was using total student that has taken IQ test.The analysis was using Fisher Exact method with significance is 0,05. The result of this research showed that there is no association between involvement in agriculture activity (p=0,375), playing habit (p=0,237), existence of crops around the house (p=0,209), existence of pesticide inside the house (p=1,000), personal hygiene (p=0,237), nutrition status (p=0,753), time of exposure (p=0,224), and period of exposure (p=0,128) with elementary children’s IQ.The conclusion from this research is as much as 66,7% children have high level IQ, but there is a significane differences of IQ between children who live around agriculture and who live not around agriculture. To avoid more child’s health issue consequences of pesticide exposure, Department of Health can give information at school to children about pesticide and personal hygiene.